Imaging for oncologic staging and follow-up: review of currentmethods and novel approaches - Cademartiri, F.; Luccichenti, G.; Maffei, E.; Fusaro, et al., M. (Acta Biomedica Atenei Parmensis, 2009)
Purpose: To review the current radiological methodologies and guidelines for staging and follow-up in oncology, and to give a perspective based on the available new technologies in oncologic radiology. Materials and Methods: The literature on cancer radiologic quantification in diagnostic phase and follow-up has been reviewed. The main concepts and guidelines (official and non-official) have been extracted taking into account the period of publication and the available technology. The current World Health Organization (WHO) and Response Evaluation Criteria In Solid Tumors (RECIST) guidelines have been critically evaluated on the basis of technical literature on quantitative radiology applied to oncology. Pitfalls of previous and current guidelines have been exploited on the basis of currently available techniques for quantification. Results: Errors due to operator, scanner, software, and measurement technique inconsistency are all together far more relevant than the recognized thresholds applied for detecting therapeutic response. For this reason the volumetric assessment of cancer disease should be introduced. Conclusion: Even though the technical constraints are still prominent in the clinical practice, the design of clinical trials should be planned taking into account these new volumetric quantitative techniques.